ナンキョク・ショウワキチ フキン ノ キョクチ ジシン - 神沼, 克伊; カミヌマ, カツタダ; 金尾, 政紀; カナオ, マサキ; Kaminuma, Katsutada; Kanao, Masaki (1997)
P(論文) 南極・昭和基地(69°S, 39°E)は東南極大陸盾状地の縁に位置している。そこでの地震観測は1959年に始まった。地震の記録の読みとり結果は, 世界の地震観測網の一点として, 震源決定に利用されており, 1968年以来毎年JARE Data Reportsの一つとして, 国立極地研究所から出版されている。1990-1996年の7年間に, 8個の局地地震が昭和基地の短周期地震計で記録された。この地震活動度は臨時に設置した三点地震観測網により, 局地地震の震源決定がなされた1987-1989年の3年間に比較して極めて低いといえる。また1996年9月25日, マグニチュード4.6のプレート内地震が, 昭和基地の北東400kmの地点で発生した。昭和基地から500km以内で, このような大きな地震が起こったのは, 昭和基地の開設以来40年間で初めてである。 The Japanese Antarctic Station Syowa (69°S, 39°E) is located at the edge of the East Antarctic Shield area. Seismic observations at Syowa Station were started in 1959. Phase readings of earthquakes have published by the National Institute of Polar Research as one of the JARE Data Report once a year since 1968. Eight local earthquakes were detected empirically on short-period seismographs at Syowa Station in 1990-1996. The seismicity during that period was very low compared with that in 1987-1989 when local earthquake locations were determined by the tripartite seismic array. An intraplate earthquake occurred about 400km north-east of Syowa Station on September 25,1996 of magnitude 4.6. This earthquake was the biggest one and the first which locates within 500km of Syowa Station during the last four decades. departmental bulletin paper